Empoderamento de empreendedoras pretas e pardas clientes do CREDIAMIGO - Ribeiro, Cicero Leonardo de Carvalho (2023)
Research carried out after the turn of the century, especially in the African andAsiancontinentsand in Latin American countries, evaluatedtheimpactofmicrocreditonwomen's empowerment, a phenomenonconsideredcomplexandinvolvingmultipledimensions. Thisworkcontributestothiscurrentofstudies in a more specificway, byinvestigatinghowblackandbrownfemale entrepreneurs who are clientsofCrediamigo, from Banco do Nordeste (BNB), thelargestmicrocreditprogram in LatinAmerica, are empowered. Fromthefemale empowerment construct, theresearchconsideredtheeconomic, domesticandpsychologicaldimensionsrecurrent in theliteraturerelatedtothetheme. The workischaracterized as a studyof a qualitativeanddescriptivenature, withthecollectionofprimary data, throughtheapplicationof a questionnaireandconductingsemi-structured interviews withseven entrepreneurs. ContentanalysiswassupportedbyAtlas.ti software. As a result, theresearchcapturedsubtledifferencesbetweenthe profiles ofthe entrepreneurs, observingsmallertraitsof empowerment amongwomen over 50 yearsold. In theeconomicdimension, thesurveyrevealedthattheintervieweeshaveautonomy in managingthe business andcontrol over financial planning, withroom for improvement in termsoftheadministrativeviewoftheiractivities. In thedomesticdimension, despitereportsofautonomyandtrustwithinthe home, partofthegroupdemonstrateddifficulty in overcomingtheestablishedpatriarchalculture, reifyingsexistthoughtsregardingthedivisionoftasksandmaintenanceofthehouse. The studyshowedthatthe entrepreneurs demonstratedcharacteristicssuch as self-confidence, self-esteemandcreativity, relatedtothepsychologicaldimensionof empowerment. In termsofthe entrepreneurs' perceptionof empowerment, it wasfoundthatCrediamigoisrecognized for theeconomicsupportof its activities as well as thepsychologicalcomfortprovidedduetothepredictability in renewingloans. The lackof direct citationstoCrediamigoassociatedwithdomestic empowerment suggeststheneed for initiativesthatcollaboratewiththisperception. Suggestions for future research include analyzingtherelationshipbetween digital inclusionandfemale empowerment in dimensionsotherthaneconomics, as well as considering cultural andreligiousaspectsoftheparticipants. The absenceofmentionsofepisodesofracismbyfemale entrepreneurs isalsosomethingthatcanbeanalyzed in furtherstudies.